The effect of gamified flipped classroom on conceptual understanding and motivation of students in learning physics - Laurio, Shiela Lyn R. (Animo Repository, 2024)
This is action research that used a gamified flipped classroom (GFC) approach to improve the students conceptual understanding and motivation in learning Physics. The study involves the integration of gamification elements into the flipped classroom model, aiming to engage student actively in outside class activities, and provide interactive learning environment during the inside class activity. The GFC approach was implemented in 2 weeks and the effect of the instruction to the student perception, motivation, and conceptual understanding in Physis was examined. The quantitative and qualitative data were gathered using both the researcher-developed and adapted survey instruments, semi-structured interviews, reflective learning journals, and scores in the pretest and posttest. The quantitative results were analyzed using paired sample t-test and Wilcoxon signed-rank test, a non-parametric statistical test, when dealing with data that does not follow a normal distribution while the qualitative data were probed using a thematic coding analysis. The data corroborated that after the GFC approach, there was a significant increase in the students’ motivation and conceptual understanding in Physics as well as positive perception of students regarding the conduct of the study. Furthermore, the thematic coding analysis showed that the modality displayed positive learning experiences, promotes understanding, challenges, and supportive features. Therefore, this study showed that it is possible to create a blended learning instruction that has capability to influence positively the student perception, improve their motivation and understanding in physics. Key Words: Gamification; Gamified Flipped Classroom; Physics Motivation, Physics Conceptual understanding, Blended Learning